2011
DOI: 10.1016/j.jad.2011.06.051
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical characteristics of Chinese patients with recurrent major depressive disorder with and without dysthymia

Abstract: BackgroundThe relationship between major depressive disorder (MDD) and dysthymia, a form of chronic depression, is complex. The two conditions are highly comorbid and it is unclear whether they are two separate disease entities. We investigated the extent to which patients with dysthymia superimposed on major depression can be distinguished from those with recurrent MDD.MethodsWe examined the clinical features in 1970 Han Chinese women with MDD (DSM-IV) between 30 and 60 years of age across China. Logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
2
11
0
1
Order By: Relevance
“…This study, initiated in 2008, has now obtained detailed clinical characteristics and information on known risk factors for MDD in 5,950 cases of recurrent MDD. An initial study published in 2011, reported results from 2,000 cases of recurrent MDD [22]. Here we extend our observations to explore the nature of the relationship between dysthymia and sensitivity to the environment.…”
Section: Introductionsupporting
confidence: 67%
“…This study, initiated in 2008, has now obtained detailed clinical characteristics and information on known risk factors for MDD in 5,950 cases of recurrent MDD. An initial study published in 2011, reported results from 2,000 cases of recurrent MDD [22]. Here we extend our observations to explore the nature of the relationship between dysthymia and sensitivity to the environment.…”
Section: Introductionsupporting
confidence: 67%
“…Although studies have defined the groups in a variety of ways (e.g., chronicity has been defined as a duration of 1 year or 2 years; non-chronic depression has been limited to major depression or also included minor depression), the results have been fairly consistent. Compared to non-chronic depression, chronic depression is characterized by higher rates of comorbid anxiety (Angst, Gamma, Rössler, Ajdacic, & Klein, 2009; Murphy & Byrne, 2012; Sang et al, 2011; Shankman et al, 2004) and personality disorders (Garyfallos et al, 1999; Markowitz et al, 1992; Pepper et al, 1995), higher levels of depressotypic cognitions (Blanco et al, 2010; Riso et al, 2003), greater suicidality (Gilmer et al, 2005; Holm-Denoma, Berlim, Fleck, & Joiner, 2006; Klein et al, 2006), and more childhood adversity and maltreatment (Angst, Gamma, Rössler, Ajdacic, & Klein, 2011; Horwitz, Widom, McLaughlin, & White, 2001; Lizardi et al, 1995; Wiersma et al, 2009). In addition, chronic depression aggregates in families of probands with chronic, but not non-chronic, depression (Klein et al, 1995, 2004; Mondimore et al, 2006) and the distinction between chronic and episodic depression is stable over time (Klein, Shankman & Rose, 2006).…”
mentioning
confidence: 99%
“…In non-AA samples, double depression was associated with more comorbid anxiety disorder (Rhebergen et al, 2012; Sang et al, 2011), panic disorder (Sang et al, 2011), various agoraphobias (Sang et al, 2011; Holm-Denoma et al, 2006), and obsessive-compulsive disorder (Holm-Denoma et al, 2006), which may explain the higher rates of disability associated with double depression compared to MDD. However, in the current study, double depression was not associated with more comorbidity, which may explain why AA who endorsed double depression reported similar disability with AA who endorsed MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to MDD, double depression is associated with more disability (Hellerstein et al, 2010). Double depression is also associated with more comorbid anxiety (Rhebergen et al, 2012; Sang et al, 2011), panic (Sang et al, 2011) and obsessive-compulsive disorders (Holm-Denoma et al, 2006), and agoraphobias (Sang et al, 2011; Holm-Denoma et al, 2006) which may explain the higher rates of disability in double depression compared to MDD. Double depression and dysthymia have similar disability and comorbidities (Hellerstein et al, 2010; Rhebergen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%